Current Management Strategies in Breast Cancer by Targeting Key Altered Molecular Players - Ali, Shazia; Mondal, Neelima; Choudhry, Hani; Rasool, Mahmood; Pushparaj, Peter N.; Khan, Mohammad A.; Mahfooz, Maryam; Sami, Ghufrana A.; Jarullah, Jummanah; Ali, Ashraf; Jamal, Mohammad S. (Frontiers in Oncology, 2016)
Breast Cancer is second largest disease affecting women worldwide. It remains the most frequently reported and leading cause of death among women in both developed and developing countries. Chemoprevention is one the promising approaches which reduces breast cancer. Tamoxifen and raloxifene are commonly used for treatment of breast cancer in women with high risk, although resistance occurs by tamoxifen after five years of therapy and both drugs cause uterine cancer and thromboembolic events. Aromatase inhibitors are coming up as potential option for prevention in treatment with adjuvant trials in practice. The combination of aromatase inhibitors along with tamoxifen can also be beneficial. For this, clinical trials based on large number of patients with optimal dose and lesser side effects have to be more in practice. Despite the clinical trials going on, there is need of better molecular models which can identify high risk population and new agents with better benefit having less side effects and improved biomarkers for treating breast cancer.